2016
DOI: 10.1111/nmo.12867
|View full text |Cite
|
Sign up to set email alerts
|

Delayed gastric emptying in diabetic rats caused by decreased expression of cystathionine gamma lyase and H2S synthesis: in vitro and in vivo studies

Abstract: The results showed that delayed GER in diabetic rats can be due to down-regulation of H S biosynthesis enzyme, CSE and suggested that a potential prokinetic role for H S to treat the delayed gastric emptying in diabetic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 30 publications
(87 reference statements)
1
15
0
Order By: Relevance
“…Analysis of qRT‐PCR results showed that mRNA expressions of CSE, and CBS in smooth muscles of jejunum, ileum, and colon in diabetic rats decreased compared to normal rats. In agreement, the authors recently have shown that the mRNA expression of CSE decreased in gastric mucosa, and muscles in alloxan‐induced diabetic rats . In a previous study, Yamane et al.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…Analysis of qRT‐PCR results showed that mRNA expressions of CSE, and CBS in smooth muscles of jejunum, ileum, and colon in diabetic rats decreased compared to normal rats. In agreement, the authors recently have shown that the mRNA expression of CSE decreased in gastric mucosa, and muscles in alloxan‐induced diabetic rats . In a previous study, Yamane et al.…”
Section: Discussionsupporting
confidence: 70%
“…NaHS at dose of 0.32 mg/kg not only decreased but also non‐significantly increased the total number, and water content of FP in normal rats. This effect could partly be due to its prokinetic effect as shown by authors in a previous study . Moreover, it has been shown that the effect of NaHS on intestinal motility was dependent on the dose of NaHS.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…In this condition, it was also found that lack of well-coordinated gastric contractions between fundic and pyloric regions impairing gastric emptying at advanced stages (Ariga et al 2008). Both delayed gastric emptying (Miyamoto et al 2001;Camilleri et al 2010;Mard et al 2016) and accelerated emptying (Phillips et al 1992;Young et al 1995;Green et al 1997) have been noticed during diabetes.…”
Section: Discussionmentioning
confidence: 99%